МОТИВАЦІЯ ЯК ЧИННИК РОЗВИТКУ БЛИЗЬКО СПОРІДНЕНОГО МОВЛЕННЯ (Педагогіка вищої та середньої школи, 2022)
The article is focuses on the specific of the motive in the development of written speech of pupils at lessons on Ukrainian language learning gas a second one.